A Correlational Study of Self-Efficacy, Marital Status, and Quality of Life in Breast Cancer Patients in Aceh, Indonesia - Liza Wahyuni; Ahyana Ahyana; Nani Safuni; Anda Kamal; Miftahul Jannah; Riski Amalia (Atatürk University, 2024)
Objective: To investigate the relationship between self-efficacy, marital status, and quality of life among Banda Aceh Hospital chemotherapy patients in Indonesia.Methods: The descriptive design was correlational with a cross-sectional approach. Sampling type of the research method used purposive sampling. The sample size of 100 breast cancer patients undergoing chemotherapy met the inclusion criteria. Instruments for this research used the Questionnaire Quality of Life-Breast Cancer (QOL-BC) and the Symptom Management Breast Cancer Self-Efficacy Scale (SMSES-BC). Multiple linear regression and spearman rank correlation were used in this analysis.Results: Self-efficacy (P<.001), marital status (P=.023), and quality of life affect breast cancer chemotherapy patients. The regression coefficient value indicated that self-efficacy (B=1.013) was the primary factor influencing the quality of life of breast cancer patients who are undergoing chemotherapy treatment.Conclusion: Self-efficacy and marital status affect breast cancer chemotherapy patients' quality of life in Aceh, Indonesia. High-self-efficacy patients manage themselves well. They avoid treatment side effects, whereas status patients are married, stay together, and improve their husbands' lives. Research findings This suggests that breast cancer patients and their families should be brought together to boost self-efficacy and motivation for treatment.